Penggunaan Metode Inquiri untuk Meningkatkan Prestasi Belajar Siswa Materi Volume Konstruksi Gedung, Jalan dan Jembatan pada Pelajaran Estimasi Biaya Konstruksi - Ririn Sandra (Tematik: Jurnal Penelitian Pendidikan Dasar, 2022)
The success of learning objectives is determined by many factors including the teacher's factor in carrying out the teaching and learning process, because the teacher can directly influence, foster and improve the intelligence and skills of students. To overcome the problems above and to achieve maximum educational goals, the role of the teacher is very important and it is hoped that the teacher has a good teaching method/model and is able to choose the right learning model and in accordance with the concepts of the subjects to be delivered. The problems that want to be studied in this research are: How to improve student learning outcomes with the application of learning the application of the Inquiry method? The objectives of this action research are: Want to know the improvement of student achievement after the implementation of learning. Application of the Inquiry method. This study uses two rounds of action research. Each round consists of four stages, namely: planning, implementation, observation, and reflection. The target of this research is the students of class XI DPIB even semester. The data obtained in the form of formative test results, observation sheets of teaching and learning activities.From the results of the analysis, it was found that students' learning motivation increased from cycle I to cycle II, namely, the average class of cycle I (68.00) cycle II (80.00). Students of class XI DPIB odd semester 2021/2022, and this learning method can be used as an alternative to learning Construction Cost Estimation.